Earable ZEN: Development of an Earphone-Type Zazen Support Wearable System. (11th December 2018) - Taniguchi, Kazuhiro; Nishikawa, Atsushi
Abstract : Meditation has been included in mental health care and the treatment of hypertension and pain. Zazen is a method of entering the meditative state. We have carried out R&D on a wearable system (earable ZEN) that casually and simply allows the subject to perform zazen without going to a temple or even having a zazen monitor present. In zazen, it is important to prepare one's breathing and posture. The earable ZEN is comprised of an earphone-type sensor (ear sensor) for measuring the breathing and posture of the user, a miniature actuator (neck belt) for communicating disturbances in the breathing and posture of the user, and a microcomputer. In an evaluation experiment, disturbance in breathing was simulated as "deep mouth breathing" and disturbance in posture was simulated as "nodding". The average accuracy value for seven healthy subjects wearing the earable ZEN was 99.9% for mouth breathing and 100% for nodding. In the same way, the average precision value was 98.7% for mouth breathing and 100% for nodding, with an average recall value of 97.1% for mouth breathing and 100% for nodding. None of the subjects considered the ear sensor and neck belt to be an obstacle to zazen.